Vergleich der biologischen Strahlenwirkung des β--Emitters 186Re mit 662 keV Photonenstrahlung auf die humane B-Zelllinie BV-173 - Staudt, Jennifer; Happel, Christian; Kranert, Wolfgang Tilman; Bockisch, Benjamin; Grünwald, Frank (Nuklearmedizin - NuclearMedicine, 2021)
Aim Aim of the study was to determine the effects of the β--emitter 186Re and 662 keV photon radiation in order to compare the biological effects of low dose rate (186Re) to high dose rate irradiation.Methods Prae-B-lymphocytes were exposed to 662 keV photon radiation or incubated with a liquid solution of 186Re. Cell count and viability were compared over the observation period of seven days, survival curves constructed and analysed at time of lowest cell-viability.Results Biphasic cell survival curves resulted for both radiation types. Survival curves were obtained at 24 h for photon radiation and 72 h for 186Re. The biphasic survival curve after photon radiation exposure can be explained by radiation hypersensitivity at doses below 1 Gy resulting in a D0 of 3.3 Gy. Doses exceeding 1.0 Gy showed a D0 of 10 Gy. The biphasic survival curve in case of 186Re incubation represents repair of sub lethal damage in the first section of the curve (D0 11.1 Gy) – in this case, biological effects of the β--emitter are attenuated by repair. Beyond an accumulated dose of 1.6 Gy, 186Re showed a steeper slope with a D0 of 4 Gy, corresponding to 2.5 times higher biological effects compared to acute photon irradiation (10 Gy).Conclusion Low dose rate radiation resulted in low biological effects at low doses. There is a threshold of accumulated dose above which biological effects of 186Re-incubation exceed those of photon irradiation.
Keywords: Biologische Strahlenwirkung; B-Zelllinie BV-173; 186Re